2007
DOI: 10.1196/annals.1381.035
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Is a Potential Environmental Factor for Crohn's Disease Induction

Abstract: Aluminum (Al) is a common environmental compound with immune-adjuvant activity and granulomatous inflammation inducer. Al exposure in food, additives, air, pharmaceuticals, and water pollution is ubiquitous in Western culture. Crohn's disease (CD) is a chronic relapsing intestinal inflammation in genetically susceptible individuals and is influenced by yet unidentified environmental factors. It is hypothesized, in the present review, that Al is a potential factor for induction or maintaining the inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 91 publications
(192 reference statements)
1
22
0
1
Order By: Relevance
“…Lerner (2007) suggested that aluminum might play a role in Crohn's disease. It is considered that the effect causing inflammation in Crohn's disease might be the interaction between aluminum and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Lerner (2007) suggested that aluminum might play a role in Crohn's disease. It is considered that the effect causing inflammation in Crohn's disease might be the interaction between aluminum and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary ideas can start with hypotheses supported by various observations that might be epidemiological or biological, some of which are displayed in Figure 2. These hypotheses have been directed towards several factors: alteration of bacterial exposure in childhood (the so-called cold-chain hypothesis); 37 impairment of the epithelial barrier by multiple food components that have included emulsifiers, 38 fermentable oligosaccharides, disaccharides, mono saccharides and polyols (FODMAPs) in Crohn's disease, 39 and foods that induce excessive nitric oxide and sulphide production in the lumen of the large bowel in ulcerative colitis; 40 and direct modulation of the control of mucosal inflammatory processes by, for example, indigestible particles [41][42][43] or exposure to various combination or individual lipids. 44,45 Many of these ideas are potentially amenable to dietary design and clinical trials.…”
Section: Identification Of Candidate Dietary Factorsmentioning
confidence: 99%
“…Ingestion of food might drive IBD via three broad mechanisms: by enabling exposure to specific microbiota in early life; 37 by enabling greater bacterial penetration of the epithelial barrier to induce inflammatory events;38,39,127 and by directly altering immune responsiveness 41,45. Abbreviations: FODMAP, fermentable oligosaccharide, disaccharide, monosaccharide and polypol; NO, nitric oxide.…”
mentioning
confidence: 99%
“…Dietary fats, high protein intake and low vitamin D may be the most important determinants. By contrast, there is no clear association of IBD and the intake of refined sugars [58] , and the effect of alimentary microparticles, such as natural contaminants (soil and dust), food additives and anti-caking agents, remains unclear [59] . Currently, the most consistent data are from the European Prospective Investigation into Cancer and Nutrition (EPIC) and concern linoleic acid.…”
Section: Diet As Etiologymentioning
confidence: 99%